2021
DOI: 10.1038/s41598-021-98504-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional and histologic imaging of urinary bladder wall after exposure to psychological stress and protamine sulfate

Abstract: To quantify the urinary bladder wall T1 relaxation time (T1) before and after the instillation contrast mixture in rats previously subjected to water avoidance stress (WAS) and/or acute exposure to protamine sulfate (PS). Female Wistar rats were randomized to receive either sham (control) or 1 h of WAS for ten consecutive days before the evaluation of nocturnal urination pattern in metabolic cages. T1 mapping of urinary bladder wall at 9.4 T was performed pre- and post- instillation of 4 mM Gadobutrol in a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Exposure to WAS increases anxiety-like behaviors, urinary frequency, and bladder hyperalgesia. Histological changes in bladder tissue from WAS-exposed rats included ulcerated areas, edema, vascular congestion, inflammatory cell infiltration, increased angiogenesis and mucosal mast cell numbers ( 2 ), and increased bladder mucosal permeability in female Wistar rats ( 167 ). Additionally, Wang et al ( 168 ), reported greater activation in brain regions of the central micturition circuit and increased engagement of portions of the micturition circuit responsive to urgency, viscerosensory perception, and its relay to motor regions coordinating imminent bladder contraction in adult female Wistar-Kyoto rats subjected to WAS to model IC.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to WAS increases anxiety-like behaviors, urinary frequency, and bladder hyperalgesia. Histological changes in bladder tissue from WAS-exposed rats included ulcerated areas, edema, vascular congestion, inflammatory cell infiltration, increased angiogenesis and mucosal mast cell numbers ( 2 ), and increased bladder mucosal permeability in female Wistar rats ( 167 ). Additionally, Wang et al ( 168 ), reported greater activation in brain regions of the central micturition circuit and increased engagement of portions of the micturition circuit responsive to urgency, viscerosensory perception, and its relay to motor regions coordinating imminent bladder contraction in adult female Wistar-Kyoto rats subjected to WAS to model IC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for over forty years that decreased host resistance [69] is a key determinant of cystitis secondary to the disruption of tissue integrity [12,65,83] or a decrease in the blood supply to the bladder either due to psychogenic stress [82] or abdominal aortic calcification [141]. A recent study reported the non-inferiority of a new triazaacenaphthy-lene antibiotic, Gepotidacin, relative to nitrofurantoin in treating uncomplicated cystitis caused by UPEC and nitrofurantoin-resistant uropathogens [33].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to men, the higher incidence of cystitis in women is generally linked to their shorter urethra and infrequent voiding [69] that thins the urothelial barrier [12,62,80] for the proximal seeding of uropathogens from the adjacent cavities of the vagina and anus [81]. It is also likely that the periodic shedding of the urothelium, observed exclusively in the females of mammals [82][83][84] may increase the inherent predisposition to cystitis [12] but frequent shedding of urothelium may be lowering the incidence of urothelial carcinoma in women [85,86].…”
Section: Cystitis Etiology and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the clearance of diffused drugs from urothelium by venous outflow [42] keeps the urothelial levels of mitomycin [43] or of Gadobutrol static with time regardless of the duration of dwell time or repeated instillation [43][44][45]. The venous clearance of Mitomycin diffusing down the concentration gradient from bladder lumen [46] ensured that urothelial Mitomycin levels remain static during the instillation period [43] but the blood levels of instilled Mitomycin [34,47] and of Gadobutrol exhibited a dynamic range during and after instillation periods(Figure 2A).…”
Section: Toxicity Associated With Intravesical Immune Checkpoint Inhi...mentioning
confidence: 99%